Sex-dependent effect of sublethal copper concentrations on de novo cholesterol synthesis in astrocytes and their possible links to variations in cholesterol and amyloid precursor protein levels in neuronal membranes - Zubillaga, Marlene (2024)
Background Cholesterol (Cho) is an essential lipophilic molecule in cells; however, both its decrease and its increase may favor the development of neurological diseases such as Alzheimer’s disease (AD). Although copper (Cu) is an essential trace metal for cells, the increased plasma concentration of its free form has been linked with AD development and severity. AD afects aged people, but its prevalence and severity are higher in women than in men. We have previously shown that Cu promotes Cho de novo synthesis in immature neurons as well as increased Cho in membrane rafts and Aβ levels in culture medium, but there are no results yet regarding sex diferences in the efects of sublethal Cu exposure on Cho de novo synthesis. Methods We examined the potential sex-specifc impact of sublethal Cu concentrations on de novo Cho synthesis in primary cultures of male and female astrocytes. We also explored whether this had any correlation with variations in Cho and APP levels within neuronal membrane rafts. Results Flow cytometry analysis demonstrated that Cu treatment leads to a greater increase in ROS levels in female astrocytes than in males. Furthermore, through RT-PCR analysis, we observed an upregulation of SREBP-2 and HMGCR. Consistently, we observed an increase in de novo Cho synthesis. Finally, western blot analysis indicated that the levels of ABCA1 increase after Cu treatment, accompanied by a higher release of radiolabeled Cho and an elevation in Cho and APP levels in neuronal membrane rafts. Importantly, all these results were signifcantly more pronounced in female astrocytes than in males. Conclusions Our fndings confrm that Cu stimulates Cho synthesis in astrocytes, both in a ROS-dependent and -independent manner. Moreover, female astrocytes displayed elevated levels of HMGCR, and de novo Cho synthesis compared to males following TBH and Cu treatments. This corresponds with higher levels of Cho released into the culture medium and a more signifcant Cho and APP rise within neuronal rafts. We consider that the increased risk of AD in females partly arises from sex-specifc responses to metals and/or exogenous substances, impacting key enzyme regulation in various biochemical pathways, including HMGCR.